Earlier Detection of Hepatitis C Virus Infection Through Routine Hepatitis C Virus Antibody Screening of Human Immunodeficiency Virus-Positive Men Who Have Sex With Men Attending A Sexually Transmitted Infection Outpatient Clinic: A Longitudinal Study. Issue 9 (September 2016) - van Rooijen, Martijn; Heijman, Titia; de Vrieze, Nynke; Urbanus, Anouk; Speksnijder, Arjen; van Leeuwen, Petra; de Vries, Henry; Prins, Maria
Abstract : Background: In 2007, routine hepatitis C virus (HCV) antibody testing was introduced for men who have sex with men (MSM) with a human immunodeficiency virus (HIV)-positive or unknown status attending a Dutch sexually transmitted infection (STI) outpatient clinic. We evaluated whether this screening resulted in additional and earlier HCV diagnoses among MSM who also attend HIV clinics. Methods: At first STI consultation, HIV-positive MSM and MSM opting-out of HIV testing (HIV-status-unknown) were tested for HCV antibodies (anti-HCV). During follow-up consultations, only previously HCV-negative men were tested. Retrospectively, STI clinic and HIV clinic HCV diagnosis dates were compared. Results: One hundred twelve (6.4%) of 1742 (95% confidence interval [CI], 5.3–7.6%) HIV-positive and 3 (0.7%) of 446 (95% CI, 0.2–2.0%) HIV-status-unknown MSM tested anti–HCV-positive at first consultation. During follow-up consultations, 32 HIV-positive (incidence HCV-positive: 2.35/100 person years (PY) (95% CI, 1.66–3.33)) and 0 (1-sided, 97.5% CI, 0.0–3.76) HIV-status-unknown MSM became anti–HCV-positive. Four (11.8%) of 34 HIV-positive MSM notified by their sexual partner of HCV tested anti–HCV-positive. Of 163 HIV-positive MSM with HCV antibodies, 78 reported a history of HCV. HCV diagnosis data at the HIV clinic was requested for the remaining 85 MSM and available for 54 MSM. Of these 54 MSM, 28 (51.9%) had their first HCV diagnosis at the STI clinic, of whom 7 concurrently with HIV. At their next scheduled HIV clinic consultation, 3 HCV cases probably would have been missed. Conclusions: The introduction of routine anti-HCV testing at the STI outpatient clinic resulted in additional and earlier HCV detection among HIV-positive MSM. Testing should be continued among HIV-positive MSM, at least for those not (yet) under the care of an HIV clinic and those notified of HCV by their sexual partner. Abstract : At the sexually transmitted infection clinic, 6.4% of human immunodeficiency virus-positive men who have sex with men tested baseline hepatitis C virus antibody positive, hepatitis C virus incidence was 2.35/100 person years and 51.9% were first detected at the sexually transmitted infection clinic (versus human immunodeficiency virus clinic).